2014
DOI: 10.1111/tpj.12491
|View full text |Cite
|
Sign up to set email alerts
|

A homolog of splicing factor SF1 is essential for development and is involved in the alternative splicing of pre‐mRNA in Arabidopsis thaliana

Abstract: SUMMARYDuring initial spliceosome assembly, SF1 binds to intron branch points and interacts with U2 snRNP auxiliary factor 65 (U2AF65). Here, we present evidence indicating that AtSF1, the Arabidopsis SF1 homolog, interacts with AtU2AF65a and AtU2AF65b, the Arabidopsis U2AF65 homologs. A mutant allele of AtSF1 (At5g51300) that contains a T-DNA insertion conferred pleiotropic developmental defects, including early flowering and abnormal sensitivity to abscisic acid. An AtSF1 promoter-driven GUS reporter assay s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
74
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(81 citation statements)
references
References 71 publications
7
74
0
Order By: Relevance
“…We recently showed that PB induces transcriptional patterns similar to those induced by a variety of abiotic stresses, and intriguingly, PB induces significant repression of splicing along with significant levels of intron retention [26]. To investigate whether GEX1A triggers similar responses, we tested its effects on the splicing of a select group of genes that are alternatively spliced under unfavorable growth conditions [2830]. For these genes, GEX1A treatment resulted in reduced splicing efficiency, leading to splicing repression with IR (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We recently showed that PB induces transcriptional patterns similar to those induced by a variety of abiotic stresses, and intriguingly, PB induces significant repression of splicing along with significant levels of intron retention [26]. To investigate whether GEX1A triggers similar responses, we tested its effects on the splicing of a select group of genes that are alternatively spliced under unfavorable growth conditions [2830]. For these genes, GEX1A treatment resulted in reduced splicing efficiency, leading to splicing repression with IR (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…U2AF65 facilitates U2 snRNP recruitment and stabilizes the interaction of U2 snRNP with the branch point of intron during assembly of spliceosomal complex A (Guth et al, 1999;Chusainow et al, 2005). Mammalian U2AF65 contains three RRMs domains and an arginine/serine-rich (RS) domain (Will & Luhrmann, 2011;Jang et al, 2014). The first and second RRMs function in the recognition of the polypyrimidine tract of intron, and the third RRM (UHM) domain interacts with SF1, which binds the branch point of intron (Corsini et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of the U2AF subunits for spliceosome assembly in mammals has been firmly established by biochemical reconstitution experiments (e.g., (15,16), among others). In contrast, SF1 selectively regulates splicing of a subset of introns (26)(27)(28)(29). One possible explanation is a transient role and rapid recycling of SF1 (30,31), such that trace amounts are sufficient to support splicing of traditional pre-mRNA substrates.…”
Section: Introductionmentioning
confidence: 99%